2012
DOI: 10.1007/s11250-012-0269-z
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of snail farming in Edo South Agricultural Zone of Edo State, Nigeria

Abstract: The study was carried out to determine the characteristics of snail farming in Edo South Agricultural Zone of Edo State Nigeria. The interview schedule was used to collect data from 60 snail farmers randomly selected from six cells in the study area. Information on the socioeconomic status of the farmers, production system, management practices and production constraints in the snail farms were elicited. The constraints were determined using a four-point Likert-type scale; a mean score of ≥ 2.5 was considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Vascular plants may have been contaminated with antimicrobial-resistant bacteria following sewage discharges or the use of irrigation water contaminated with the faeces of humans and animals reared with antibiotic abuse ( 6 ). Plant leaves, vegetables and kitchen wastes have come into common use by snail breeders as feed because formulated feeds for snails are not available on the Nigerian market ( 12 ). Furthermore, scientific studies have shown that soil is a major reservoir of antibiotic resistance genes ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vascular plants may have been contaminated with antimicrobial-resistant bacteria following sewage discharges or the use of irrigation water contaminated with the faeces of humans and animals reared with antibiotic abuse ( 6 ). Plant leaves, vegetables and kitchen wastes have come into common use by snail breeders as feed because formulated feeds for snails are not available on the Nigerian market ( 12 ). Furthermore, scientific studies have shown that soil is a major reservoir of antibiotic resistance genes ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Formulated feeds for snails are not available in the market. Therefore, it has become common practice for snail rearers to use vegetables, plant leaves and kitchen wastes to feed snails (Chah and Inegbedion, 2013). Aeromonas species are widely distributed in the aquatic environment (Palumbo, 1996, Neyts et al, 2000 and their prevalence in various water and food sources represents a significant public health threat (Wu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The study posited that a pragmatic approach to building the capacity of existing and prospective farmers should be adopted to improve the snail supply chain. Chah and Inegbedion (2012) looked into the different production systems of snail farmers in Edo State, Nigeria. Archantina archantina and Archantina marginata were found to be the most commonly reared species by the farmers with the former being 43.3 % and the latter being 26.7 %.…”
Section: Introductionmentioning
confidence: 99%